Educational Service and Quality Assurance from the Perception of Teachers and Students during COVID-19 in an Accredited and Certified Administration Degree Program (Global Journal of Science Frontier Research, 2021)
The impact of the COVID-19 pandemic has evidenced the fragility of the education system at all levels which is why the call of the United Nations through the Sustainable Development Goals SDGs Agenda 2030 specifically Goal 4 is especially relevant Additionally Pope Francis at the end of the year 2020 proposes to the world a Global Pact on Education in view of the increase of the social debt due to the unprecedented affectation of the educational system This disruption in the lives of all people due to compulsory isolation gave way to a change of era and surprised the face-to-face education supply which had to adjust to a new way of educating The capacity for resilience made it possible to evaluate analyze and visualize transformation processes in education whether in the management of the educational service and or in the teaching-learning systems Therefore this work aims to identify the perception of teachers and students regarding the educational service and quality assurance in COVID-19 time of an accredited and certified Administration career belonging to a prestigious university in Ecuador with Ignatian educational model during the year 2020
Keywords: educational service; quality; COVID-19